Using SERVQUAL to Evaluate Quality Disconfirmation of Nursing Service in Taiwan - 周守民(Shieu-Ming Chou); 陳彩鳳(Thai-Form Chen); Beth Woodard; 顏妙芬(Miao-Fen Yen) (Journal of Nursing Research, 2005)
The purpose of this study was to determine the extent of disconfirmation of the perceived quality of nursing services, and its relationship to patient's satisfaction, intent to return, and intent to recommend to others. The service dimensions were tangibles, reliability, responsiveness, assurance, and empathy, which were adopted from the Gap model of Parasuraman, Zeithaml and Berry (1985). A total of 186 subjects was tested by a modified SERVQUAI (service quality) instrument. These subjects were from 15 randomly selected medical-surgical units in a medical center in Taipei, Taiwan, Republic of China. The response rate was 92%. Descriptive statistics and multiple regression were used to analyze subjects' responses. A number of the demographic variables served as covariates in data analysis. Responsiveness was highly significant in predicting overall satisfaction with hospital service (p=.0003). Reliability was significant in predicting overall satisfaction with nursing care (p＜.00005) and intent to return. Empathy was a highly significant predictor of intent to recommend.